The Influence of Maternal and Child Characteristics with a History of Low Birth Weight (LBW) on Stunting Incidence in Toddlers in East Nusa Tenggara Province (Analysis of Riskesdas 2018 Data) - Inna Viva Sa'adah (Jurnal Indonesia Sosial Sains, 2024)
Stunting is a chronic nutritional problem in children under five years of age characterized by shorter height than their peers. Low birth weight (LBW) is a public health indicator because it is closely related to mortality, morbidity and the incidence of malnutrition in children, one of which is stunting. Reducing the prevalence of stunting is one of the goals in the Sustainable Development Goals (SDGs). The prevalence of stunting in East Nusa Tenggara Province is 42.6% and the highest in Indonesia. This researche aims to determine socio-demographic factors, especially maternal characteristics and child characteristics, on the incidence of stunting with a history of LBW in toddlers aged 6-59 months in East Nusa Tenggara Province. The sample of this study was toddlers with a history of LBW who came from the 2018 riskesdas data. Data were analyzed using bivariate analysis with chisquare test and multivariate with binary logistic regression. Logistic regression results revealed that toddlers aged 12-36 months had a 0.27 times higher risk of stunting, while mothers working as farmers had a 0.29 times higher risk compared to other occupations. The research found significant associations between the mother's education (p=0.048), mother's occupation (p=0.023), and toddler's age (p=0.006) with stunting incidence. Maternal age and child gender showed no significant effects. These findings highlight the need for targeted nutritional interventions focusing on identified socio-demographic risk factors.